Evaluation of schistosomula crude antigen (SCA) as a diagnostic tool for Schistosoma mansoni in low endemic human population - Oyetunde Timothy Oyeyemi (Nature Portfolio, 2021)
Abstract The study aimed to determine the potential of schistosomula crude antigen (SCA) as a diagnostic target for anti-S. mansoni antibody detection. Cercariae were transformed into schistosomula, homogenized through sonication, and then centrifuged to obtain the SCA. SCA was evaluated using ELISA and dot blots immunoassays on 30 S. mansoni infected sera samples obtained from chronic patients and 30 non-infected humans’ sera samples. Either Kato-Katz or saline gradient method or both were employed as the diagnostic reference. Dot blots immunoassay was further performed on protein eluted from 10 to 12 kDa immunoreactive band identified by Western blot analysis. The area under the ROC curve was 0.95 (AUC 0.95, CI 0.88–1.01, p < 0.0001). The sensitivity and specificity of SCA-ELISA and dot blots assays were 96.67% and 86.67% respectively. The human IgG-specific response against SCA was significantly higher in S. mansoni infected individuals (OD = 0.678 ± 0.249) compared to the non-infected population (OD = 0.235 ± 0.136) (p < 0.0001). Our study showed that SCA and its 10–12 kDa component could be useful as diagnostic tools for chronic schistosomiasis.